2015
DOI: 10.1021/acs.nanolett.5b00055
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Electrostatic and Quantum Capacitances of Few Layered Graphenes through Plasma Processing

Abstract: It is shown that charged defect generation, through argon ion-based plasma processing, in few layer graphene, could substantially enhance the electrical capacitance for electrochemical energy storage. Detailed consideration of the constituent space charge and quantum capacitances were used to delineate a new length scale, correlated to electrically active defects contributing to the capacitance, and was found to be smaller than a structural correlation length determined through Raman spectroscopy. The study of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 31 publications
1
42
0
Order By: Relevance
“…Which was deconvoluted to yield the Space-Charge Capacitance (C SC ) and the Quantum Capacitance (C Q ) with corresponding values of two-dimensional carrier density (n 2D,0 ), volumetric charge density (n), Fermi-velocity (ν F ) and the Fermi energy (E F ). 143 Reprinted with permission from Narayanan et al, Nano Lett. 15, 3067 (2015).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Which was deconvoluted to yield the Space-Charge Capacitance (C SC ) and the Quantum Capacitance (C Q ) with corresponding values of two-dimensional carrier density (n 2D,0 ), volumetric charge density (n), Fermi-velocity (ν F ) and the Fermi energy (E F ). 143 Reprinted with permission from Narayanan et al, Nano Lett. 15, 3067 (2015).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Defects in material science and engineering are often perceived as performance limiters, but in the case of 2D materials, defect engineering could provide a way to overcome many roadblocks and forge new frontiers. In this regard, others and we have shown that defects in 2D materials (e.g., dopants, vacancies) can provide an excellent handle to control material properties [5][6][7][8]. Specifically, we have shown that defects such as vacancies and N dopants in graphene could be used to control the electron-electron and electron-phonon scattering pathways [8].…”
Section: Introductionmentioning
confidence: 88%
“…Specifically, we have shown that defects such as vacancies and N dopants in graphene could be used to control the electron-electron and electron-phonon scattering pathways [8]. These results provided critical breakthroughs for improving the quantum capacitance of graphene and doping graphene without compromising its intrinsic characteristics [6]. Defects also play a vital role in improving the properties of the so-called "beyond graphene" 2D materials.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations